Bacterial Glycosulphatases and Sulphomucin Degradation - Anthony M Roberton; Damian P Wright (Canadian Journal of Gastroenterology)
The presence of a high bacterial population in a region of the gastrointestinal tract is usually associated with the secretion of sulphomucins into the mucus gel covering that region. The term 'sulphomucin' is a histochemical description of the staining properties of mucin. At present this term can only be qualitatively related to the percentage of sulphate in the mucin molecule, which makes the term difficult to use in a biochemical and functional sense. Sulphomucins are thought to carry out the normal functions attributed to mucins; in addition, heavy sulphation rate-limits the degradation of mucins by bacterial mucin-degrading glycosidases. A number of mucin-specific glycosulphatases have been reported in bacteria, although only two such enzymes have been purified. These enzymes remove part of the sulphate content from sulphomucins and make them more susceptible to further enzymic degradation. The variety of chain locations and sugar attachment sites of sulphate esters on the mucin oligosaccharides, taken together with the data on the enzymes, suggest there will be a spectrum of bacterial glycosulphatases, with different properties, cellular locations and substrate specificities. Bacterial glycosulphatases have the potential to modify sulphated glycoconjugates at mucosal surfaces and should prove useful as biochemical tools for the study of sulphated glycoconjugates.